2011
DOI: 10.1007/978-94-007-2240-8_10
|View full text |Cite
|
Sign up to set email alerts
|

European Ground Water Geochemistry Using Bottled Water as a Sampling Medium

Abstract: To obtain a fi rst impression of the geochemistry and quality of European ground water bottled mineral water was used as a sampling medium. In total, 1,785 bottled waters were purchased from supermarkets of 40 European countries, representing 1,247 wells/drill holes/springs at 884 locations. All bottled waters were analysed for 72 parameters at the laboratories of the Federal Institute for Geosciences and Natural Resources (BGR) in Germany. The geochemical maps give a fi rst impression of the natural variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The median values for the PTE determined in bottled waters from the present study were, in general, lower than those of the British and continental EU (Czech Republic, Slovakia, Finland, France, Germany and Italy) bottled waters analyzed by Felipe-Sotelo et al ( 2015) [8]. The median values for As (0.293 µg L −1 ), Cd (0.015 µg L −1 ), and Cr (0.257 µg L −1 ) from the present study were slightly higher compared to German and other EU mineral bottled waters as reported by Birke et al [19] (0.190 µg L −1 for As, 0.0032 µg L −1 for Cd, and 0.121 µg L −1 for Cr) and Demetriades et al [38] (0.235 µg L −1 for As and <0.2 µg L −1 for Cr). Frengstad et al [18] determined the elemental composition (58 elements) of bottled mineral and spring waters from Norway, Sweden, Finland and Iceland.…”
Section: Content Of Major and Trace Elements In Bottled Waterssupporting
confidence: 52%
See 1 more Smart Citation
“…The median values for the PTE determined in bottled waters from the present study were, in general, lower than those of the British and continental EU (Czech Republic, Slovakia, Finland, France, Germany and Italy) bottled waters analyzed by Felipe-Sotelo et al ( 2015) [8]. The median values for As (0.293 µg L −1 ), Cd (0.015 µg L −1 ), and Cr (0.257 µg L −1 ) from the present study were slightly higher compared to German and other EU mineral bottled waters as reported by Birke et al [19] (0.190 µg L −1 for As, 0.0032 µg L −1 for Cd, and 0.121 µg L −1 for Cr) and Demetriades et al [38] (0.235 µg L −1 for As and <0.2 µg L −1 for Cr). Frengstad et al [18] determined the elemental composition (58 elements) of bottled mineral and spring waters from Norway, Sweden, Finland and Iceland.…”
Section: Content Of Major and Trace Elements In Bottled Waterssupporting
confidence: 52%
“…Its chemical composition is altered by the presence of pegmatite, as reported by Petrović et al (2010) [37]. Spring water Laqueuille was characterized by higher As, V, and K concentrations, where K may be related to the occurrence of alkaline rocks, especially near volcanic centers, and V confirming the presence of volcanism and basaltic rocks [38]. Indeed, the Laqueuille spring water is captured near Parc Naturel Regional des Volcans d'Auvergne in France.…”
Section: Content Of Major and Trace Elements In Bottled Watersmentioning
confidence: 61%
“…Vanadium is an essential element for human life, and its consumption in a low dose may have a positive effect on human health [98]; yet, acute vanadium poisoning may result in several disorders, including palpitations, coronary insufficiency, and reduced neurobehavioral activities [99,100]. Due to its toxicity, the threshold for vanadium's concentration in drinking water has been set at 140 µg L −1 by Italian law [80]; lower values are prescribed in some Balkan countries [81] (Table 1).…”
Section: Contaminantmentioning
confidence: 99%
“…These may often not be particularly up to date, but they provide a rough guide on the likely chemical composition of bottled waters. There has also been a lot of research into the testing of bottled mineral water for mineralisation [26][27][28][29]. As can be seen in Figure 1, the choice of bottled mineral water allowed very different types of water to be selected.…”
Section: Introductionmentioning
confidence: 99%